2020
DOI: 10.11646/zootaxa.4728.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and taxonomy of the intertidal patellogastropod limpets of  the mainland Indian coastline

Abstract: We report the diversity, distribution and taxonomy of patellogastropod species from the entire mainland Indian coastline. A total of 77 coastal areas with rocky outcrops in the sandy shoreline, covering the entire mainland Indian coastline, were surveyed seasonally (four times a year) during December 2014 to December 2016. Coastal habitat characteristics and the diversity of all groups of limpets from the intertidal areas were recorded. Specimens were identified by external morphological shell and gill charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As they are limited to a species or genus, it is useful to identify the feeding habitat of the animal (Vakani et al, 2020). Radula reveals the variances in intraspecific level better than the morphology of shell, foot, and other significant characteristics (Mutlu, 2004;Mutaf and Aksit, 2009;Vakani et al, 2020). Only through radular morphology, we could point out similarities in the family level as well as in the species level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As they are limited to a species or genus, it is useful to identify the feeding habitat of the animal (Vakani et al, 2020). Radula reveals the variances in intraspecific level better than the morphology of shell, foot, and other significant characteristics (Mutlu, 2004;Mutaf and Aksit, 2009;Vakani et al, 2020). Only through radular morphology, we could point out similarities in the family level as well as in the species level.…”
Section: Discussionmentioning
confidence: 99%
“…This feeding organ is very significant in molluscan, especially in the taxonomy of the gastropod. As they are limited to a species or genus, it is useful to identify the feeding habitat of the animal (Vakani et al, 2020). Radula reveals the variances in intraspecific level better than the morphology of shell, foot, and other significant characteristics (Mutlu, 2004;Mutaf and Aksit, 2009;Vakani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest species diversity was recorded at the rocky shore. Twenty-four species belonging to 18 families of bryozoans were identified from the rocky intertidal zones of Gujarat and Maharashtra by Venkatraman et al (2018) and 23 species of limpets were reported from the same coastal stretch by Vakani and Kundu (2018) and Vakani et al (2020). Vadher et al (2020) provided a checklist of 95 sea slug species from the intertidal region of Gujarat coast.…”
Section: Rocky Intertidalmentioning
confidence: 99%